PENGEMBANGAN MEDIA COLORED PAPER DALAM MENINGKATKAN COMMUNICATION SKILLS PADA PEMBELAJARAN IPAS SISWA KELAS IV SEKOLAH DASAR - Maharani Nurul Ain; Muhammad Rifqi Rijal; Imas Mastoah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low level of communication skills among fourth-grade students in Science and Social Studies (IPAS) remains a significant challenge in the learning process. This condition is reflected in students' lack of confidence in expressing opinions, asking questions, and responding to their peers' ideas, which is influenced by the predominance of conventional teaching methods and the limited use of instructional media. This study focuses on developing Colored Paper as an instructional medium that is both feasible and effective in improving the communication skills of fourth-grade students in IPAS. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the product was assessed through validation by subject matter experts, language experts, and media experts, while its effectiveness was evaluated based on teacher and student responses, as well as comparisons of pre-test and post-test results using N-Gain analysis. The findings indicate that the Colored Paper instructional media achieved an overall feasibility score of 88.33%, categorized as highly feasible, based on evaluations from subject matter experts (90%), language experts (88%), and media experts (86%). Student responses reached 97.2%, while teacher responses were 88%, both of which were categorized as very good. The effectiveness of the instructional media was demonstrated by an increase in the students' average communication skills score from 12.64 on the pre-test to 23.72 on the post-test, with an N-Gain score of 0.902 (90.2%), which falls into the high category. Therefore, the Colored Paper instructional media is considered highly feasible and effective in improving the communication skills of fourth-grade students at SDN Lawanggintung 2 Bogor in the IPAS subject. ABSTRAK Rendahnya keterampilan komunikasi siswa kelas IV pada mata pelajaran IPAS masih menjadi permasalahan dalam proses pembelajaran. Kondisi ini ditunjukkan oleh rendahnya keberanian siswa dalam menyampaikan pendapat, mengajukan pertanyaan, maupun memberikan tanggapan terhadap ide teman, yang dipengaruhi oleh pembelajaran yang masih didominasi metode konvensional serta penggunaan media pembelajaran yang kurang variatif. Penelitian ini berfokus pada pengembangan media pembelajaran Colored Paper yang layak dan efektif untuk meningkatkan keterampilan komunikasi siswa kelas IV pada mata pelajaran IPAS. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE, yang meliputi lima tahapan, yaitu Analysis, Design, Development, Implementation, dan Evaluation. Kelayakan produk dinilai melalui validasi ahli materi, ahli bahasa, dan ahli media, sedangkan efektivitas media diuji melalui respons guru, respons siswa, serta perbandingan hasil pre-test dan post-test menggunakan analisis N-Gain. Hasil penelitian menunjukkan bahwa media Colored Paper memperoleh rata-rata persentase kelayakan sebesar 88,33% dengan kategori sangat layak, yang terdiri atas penilaian ahli materi sebesar 90%, ahli bahasa 88%, dan ahli media 86%. Respons siswa terhadap penggunaan media mencapai 97,2%, sedangkan respons guru sebesar 88%, keduanya berada pada kategori sangat baik. Keefektifan media ditunjukkan oleh peningkatan nilai rata-rata keterampilan komunikasi siswa dari 12,64 pada pre-test menjadi 23,72 pada post-test, dengan nilai N-Gain sebesar 0,902 (90,2%) yang termasuk kategori tinggi. Dengan demikian, media pembelajaran Colored Paper dinyatakan sangat layak dan efektif untuk meningkatkan keterampilan komunikasi siswa kelas IV SDN Lawanggintung 2 Bogor pada mata pelajaran IPAS.